2012
DOI: 10.1016/j.juro.2012.07.043
|View full text |Cite
|
Sign up to set email alerts
|

Association of Tumor Size, Location, R.E.N.A.L., PADUA and Centrality Index Score with Perioperative Outcomes and Postoperative Renal Function

Abstract: Each scoring system outperformed tumor size and location, and may be useful when describing the surgical complexity of renal tumors treated with partial nephrectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
85
0
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(94 citation statements)
references
References 22 publications
1
85
0
8
Order By: Relevance
“…Unfortunately, some previous reports have shown that the C index, PADUA and R.E.N.A.L. nephrometry score cannot predict postoperative RFL, 10,12,13 although a few previous studies have shown that all three scoring systems are significantly associated with the percentage change in creatinine level, 14,15 as well as warm ischemia time and tumour size. 14 Therefore, in the present study, we developed a highly accurate index to predict the postoperative RFL following LPN.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Unfortunately, some previous reports have shown that the C index, PADUA and R.E.N.A.L. nephrometry score cannot predict postoperative RFL, 10,12,13 although a few previous studies have shown that all three scoring systems are significantly associated with the percentage change in creatinine level, 14,15 as well as warm ischemia time and tumour size. 14 Therefore, in the present study, we developed a highly accurate index to predict the postoperative RFL following LPN.…”
Section: Discussionmentioning
confidence: 93%
“…Some anatomical scoring systems were reported to be able to predict the technical difficulty of LPN, 10 including the risk of surgical complications 8,11 and ischemia time 12 during LPN. The present study indicated that the m-CI might predict the operative time and ischemia time of LPN and blood loss during LPN, which should represent the surgical difficulty of LPN.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 PADUA scores have been validated to predict warm ischemic time (WIT) and perioperative complications for open, laparoscopic, and robot-assisted partial nephrectomy (RAPN). [2][3][4][5][6] Functional outcome is an important parameter during the surgical planning of renal tumours. Numerous welldocumented variables have been associated with postoperative renal function.…”
Section: Introductionmentioning
confidence: 99%